List Coloring Problems - เจริญพานิชเสรี วงศกร; ฉันทวีโรจน์ พวงรัตน์ (KKU Science Journal, 2014)
A list assignment L of a graph G is a function which assigns a set of colors to all vertices and G is called L-colorable if each vertex v can be colored by using color from L(v) and adjacent vertices receive distinct colors. In this article, definitions related to list assignment problems are introduced. Then some research of list assignment problems is proposed; for example, a characterization of 2-choosable graphs, a characterization of 3-choosable complete bipartite graphs and a list assignment such that prevents K7,7 and K7,8 from being 3-choosable. Finally, topics of possible future research are presented.